Automatic code generation of AUTOSAR compliant HMI applications - Afshoon, Samira; Ghavibazou, Maryam (My University, 2014)
Today in automotive industry the trend is moving toward use of Human Machine Interfaces for a variety of purposes from designing interfaces for infotainment systems till instrument clusters. Mecel Populus Suite is a complete tool chain for design, development and deployment of the user interfaces for distributed embedded systems [5]. The current version of this product does not support automatic communication with application under AUTOSAR standard. The objective of this master thesis is to investigate the possibility of auto-generating AUTOSAR compliant interfaces for the Mecel Populus functional units and implementing an appropriate solution which can serve this purpose and provide an easy procedure for data communication between these two. The investigation phase consists of proposing a simple process for data mapping and data transmission between Populus and AUTOSAR while the implementation phase consists of providing a user friendly plugin for the Mecel Populus Suite which can offer the expected functionality.
Keywords: Data- och informationsvetenskap; Computer and Information Science